Back scattering response from single, finite and infinite array of nonlinear antennas based on intelligent water drops algorithm. Issue 6 (24th October 2019) - Bahrami, Amir; Ostadzadeh, Saeed Reza
Abstract : Purpose: The purpose of this paper is to calculate the back scattering response from single, finite and infinite arrays of nonlinear antennas like the case where the antennas are exposed to high-value signals such as lightning strokes. Design/methodology/approach: In this paper, the authors have used a recently introduced optimization technique called intelligent water drop. Findings: The results exhibit that the method used by the authors is faster and more accurate than other conventional optimization algorithms, i.e. particle swarm optimization and genetic algorithm. Originality/value: A new optimization algorithm is used to solve nonlinear problem accurately and sufficiently. Although the technique is not confined to the mentioned examples in the paper, it can be applied to other nonlinear circuits.